Identification Insidence Of Premature Rupture Of The Membranes Risk Factors - Rahardjo, Abdi Malik; Tunjungsari, feny (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Premature rupture of membranes can cause several problems for the mother and for the fetus. Significantly causing neonatal and maternal deaths in countries with high and low incomes, besides that the burden of PROM itself is not limited to maternal and neonatal but also a decrease in the country's economic power due to the need for drugs, hospital care, and burdens for health workers. Failure to increase birth attempts by 2035 will result in around 116 million deaths and 99 million living with disabilities , moreover complications from PROM namely low birth weight, asphyxia, neonatal infection , sepsis, chorioamnionitis . Therefore, paying attention to pregnant women with risk factors for premature rupture of membranes and looking for possibilities that underlie these risks is very important in preventing and early detection of premature rupture of membranes. The research method uses literature studies from several national and international journals obtained from 30 reference sources through searches on PubMed and Google Scholar which were published within the last 5 years. A total of 30 full-text articles were obtained that met the inclusion criteria and contained several risk factors associated with premature rupture of membranes (PROM). Risk factors for premature rupture of membranes include age, parity, smoking, anemia, history of BV, occupation, antenatal care , vaginal dysbiosis , history of CS, history of premature rupture of membranes, history of premature birth, history of abortion, spacing of pregnancies, history of HIV, group infection B streptococcus (GBS), amniotic fluid volume, urinary tract infection. Identification of risk factors for premature rupture of membranes can reduce the incidence and associated mortality of the disease. So that it can reduce the level of mortality and morbidity in mothers and children. Keywords : premature rupture of membranes, PROM, risk factors.